Politik Kiai Dan Resistensi Sosial - Vellayati Hajad (Universitas Teuku Umar, 2015)
Today many emerging Kiai who play outside the Pesantren and leaving its main task as an educator in Islamic education institutions and engage in practical politics. The actions taken by Kiai (whatever it is) will lead to a variety of social and political implications are very interesting to examine scientifically. Furthermore, this writing tried to describe an important finding that Kiai involvement in politics, even though on the one hand advantageous for Kiai and the pesantren, but on the other hand decrease the legitimacy of Kiai and bring resistance of society.Keywords: Kiai, Political, Social, Resistant